Quantum metrology of two-photon absorption - Muñoz, Carlos Sánchez; Frascella, Gaetano; Schlawin, Frank (Optics InfoBase Conference Papers, 2022)
We consider the measurement of two-photon absorption (TPA) cross sections as a quantum metrology problem. We establish the scaling behaviour of nonclassical light sources for precision measurements of TPA cross sections and assess different measurement strategies. Finally, the impact of single-photon losses is discussed.
CRIS-Team Scopus Importer:2022-09-09